Kubera portrayed on the enclosure wall - Temples of India Project Team (Jio Institute, 2024)
In addition to the main deities and pantheon, several sculptures of dikpalas (guardians of directions) are also present. One of these dikpalas is Kubera, with two sculptures visible on the enclosure wall. Both depictions show Kubera crowned, with four arms and standing. He holds a money bag in his upper arms, while his lower right hand is in the varada hasta (boon-giving gesture) in both sculptures. In his other lower arm, he carries a kamandalu (water pot) in one sculpture and a bowl-like container in another. The only distinction between the two sculptures is that one portrays a mature male deity with a beard and moustache, while the other depicts a youthful deity with a slim, toned body.